1983
DOI: 10.2214/ajr.140.2.245
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some contrast agents in the lung: an experimental study in the rat and dog

Abstract: Radiographicand histologic studies were carried out in rats and dogs after the instillation of Barosperse, Hypaque-35%, metrizamide, MP1001 3 (a nonionic iodinecontaining agent), and isotonic saline into the lungs of these animals. In addition, blood gases were examined using these agents in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
2
5

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 3 publications
0
27
2
5
Order By: Relevance
“…In animals LOWS contrast media produced less lung damage than hypertonic water soluble contrast media or barium suspensions [12,20]. The introduction of barium [19] and hypertonic [13] contrast media into the peritoneum produces inflammatory changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In animals LOWS contrast media produced less lung damage than hypertonic water soluble contrast media or barium suspensions [12,20]. The introduction of barium [19] and hypertonic [13] contrast media into the peritoneum produces inflammatory changes.…”
Section: Discussionmentioning
confidence: 98%
“…Barium is contraindicated if free peritoneal, mediastinal or pleural leak is susPected [6,7,18,19]. Hypertonic contrast media exacerbate dehydration [10,11] and cause inflammation and pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have therefore been performed in rats [17-19, 22, 30, 31], guinea pigs [23], rabbits [20,21] and dogs [18] to assess the damage of aspiration of commonly used watersoluble contrast media. As a result, it has been established that although some of these contrast media are not suitable to use for intrabronchial diagnostic procedures, other nonionic media did not cause harm to the respiratory system [17][18][19][20][21][22][23][24]31]. Similarly, LARSEN et al [25] reported that nonionic iso-osmolar contrast media, including iodixanol, when instilled intratracheally did not induce lung tissue damage or lead to respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…There are contradictory reports on the seriousness of adverse effects when commonly used contrast media are aspirated in the lungs [17][18][19][20][21][22]. However, it has been shown that nonionic and isotonic agents are well tolerated and cause fewer pulmonary complications than ionic and hyperosmolar agents [17-19, 23, 24].…”
mentioning
confidence: 99%
“…Because of the inert character of barium sulfate no lung injury characterized by polymorphonuclear neutrophil leukocytes sequestration and edema usually seen after acid aspiration occurs [4,5]. However, there are reports of acute inflammation of the bronchial wall after barium aspiration which have been attributed to high density preparations (250% w/v) of barium sulfate [6,7], but have also been reported using lower density barium sulfate preparations [8]. Moreover, hypersensitivity reactions caused by one of the many additives to commercial barium preparations have been observed [6].…”
Section: Discussionmentioning
confidence: 99%